Pilkada Amidst a Pandemic: The Role of The Electronic Word of Mouth in Political Brand and Voting Intention - Linda Fitriani; Jono M Munandar; Ujang Sumarwan (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
The Regional Head Election campaign frequently uses electronic Word of Mouth (eWOM) communication because of social media's growth and the Covid-19 pandemic that took place during the election year. In commercial brands, eWOM impact has influence brand equity and purchase decisions. However, in political brands, this has not been proven. Therefore, by using the regional head candidate of Purbalingga Regency as a political brand, this study examines the effect of eWOM on developing candidate brand equity and relates it to voting intention. Brand equity using a brand pyramid model with brand equity forming variables consisting of a candidate brand awareness, a candidate brand performance-imagery, a candidate brand judgment-feelings, and a candidate brand resonance. The study involved 260 respondents who are people of Purbalingga Regency who may vote and use social media. The sampling method used was purposive sampling by conducting direct interviews with respondents. Data were analyzed using Structural Equation Model Partial Least Square (SEM PLS) analysis. The results showed that electronic Word of Mouth has a positive and significant effect on brand equity development variables. Developing brand equity affects the voting intention on candidate brand awareness and candidate brand resonance. The Result of this study found electronic Word of Mouth to have no direct influence on voting intention.